The Influence of TikTok Marketing and Online Customer Reviews on Generation Z's Purchase Intention: Empirical Evidence from Coffee Shop Consumers in Medan City, Indonesia - Muhammad Ridwan Verinanda; Imam Gunanjar; Rahmat Maulidan; Rico Syahputra; Ulfa Utari (Jurnal Investasi Islam, 2026)
This study aims to analyze the influence of TikTok Marketing and Online Customer Review on Generation Z purchase intention toward coffee shops in Medan City, Indonesia, while providing empirical evidence in the context of digital consumer behavior in the coffee shop industry. This research employed a quantitative approach with a survey method involving 100 respondents selected through purposive sampling, consisting of Generation Z consumers who had visited coffee shops in Medan, seen coffee shop promotions on TikTok, and read online customer reviews; the data were analyzed using multiple linear regression with IBM SPSS Statistics 27. The findings indicate that TikTok Marketing has a positive and significant effect on purchase intention (β = 0.458; p < 0.001), while Online Customer Review also has a positive and significant effect on purchase intention (β = 0.387; p < 0.001); both variables simultaneously explain 61% of the variation in purchase intention, suggesting that creative TikTok content functions as an initial stimulus that attracts consumer attention, whereas online reviews strengthen consumer trust before making a purchase decision, and these findings are consistent with the Theory of Planned Behavior and Information Adoption Model. In conclusion, the integration of TikTok Marketing and Online Customer Review is an effective digital marketing strategy for improving coffee shop competitiveness in Medan; therefore, coffee shop managers should optimize creative content and customer experience management to generate positive reviews, while future research is recommended to include additional variables such as brand image, store atmosphere, and influencer marketing with a broader sample coverage.